2020
DOI: 10.20944/preprints202012.0343.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Micronutrients, Non-Nutrients and Mediterranean Diet: A Potential Protective Role Against COVID-19 through Modulation of PAF Actions and Metabolism

Abstract: The new coronavirus disease 2019 (COVID-19) pandemic is an emerging situation with high rates of morbidity and mortality, in the pathophysiology of which inflammation and thrombosis are implicated. The disease is directly connected to the nutritional status of patients and a well-balanced diet is recommended by official sources. Recently, the role of platelet activating factor (PAF) was suggested in the pathogenesis of COVID-19. In the present review several micronutrients (vitamin A, vitamin C, vitamin E, vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 175 publications
(224 reference statements)
0
4
0
Order By: Relevance
“…54,55 Indeed, micronutrients, non-nutrients, and Mediterranean diet have been proposed to exert a potential protective role against COVID-19 through modulation of PAF actions and metabolism. 56 To optimize vitamin D, a few minutes of sunlight exposure should be considered along with vitamin D-rich and -enriched foods. 11 Although several lines of evidence indicate a role of vitamin D supplementation in acute respiratory tract infection, 57 and ongoing studies with COVID-19 patients have included vitamin D as an adjunct therapeutic line in their protocol, 41 the supplementation with vitamin D is not officially recommended for COVID-19 prevention and/or treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…54,55 Indeed, micronutrients, non-nutrients, and Mediterranean diet have been proposed to exert a potential protective role against COVID-19 through modulation of PAF actions and metabolism. 56 To optimize vitamin D, a few minutes of sunlight exposure should be considered along with vitamin D-rich and -enriched foods. 11 Although several lines of evidence indicate a role of vitamin D supplementation in acute respiratory tract infection, 57 and ongoing studies with COVID-19 patients have included vitamin D as an adjunct therapeutic line in their protocol, 41 the supplementation with vitamin D is not officially recommended for COVID-19 prevention and/or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and antithrombotic effects of Mediterranean diet as a whole and its several individual components may act as a “weapon” against the cytokine storm of the disease53 and the activation of newly defined key molecules of COVID-19 pathogenesis, such as platelet activating factor (PAF) 54,55. Indeed, micronutrients, non-nutrients, and Mediterranean diet have been proposed to exert a potential protective role against COVID-19 through modulation of PAF actions and metabolism 56…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, researchers have investigated preventive and therapeutic effects of micronutrients on SARS-COV-2 infection as a novel concept. 13 A recent study showed that there is a regulatory effect of high-dose vitamin C on COVID-19-associated cytokine storm. 14 In addition, evidence showed that coping with micronutrient deficiencies such as vitamins D, E, zinc, and magnesium is essential in the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%